Zika virus induced microcephaly and aberrant hematopoietic cell differentiation modeled in novel neonatal humanized mice - Schmitt, Kimberly; Curlin, James Z.; Remling-Mulder, Leila; Aboellail, Tawfik; Akkina, Ramesh (Frontiers in Immunology, 2023)
Introduction Immunocompetent and immunocompromised murine models have been instrumental in answering important questions regarding ZIKV pathogenesis and vertical transmission. However, mimicking human congenital zika syndrome (CZS) characteristics in these murine models has been less than optimal and does not address the potential viral effects on the human immune system. Methods Here, we utilized neonatal humanized Rag2-/-γc-/- mice to model CZS and evaluate the potential viral effects on the differentiation of human hematopoietic stem cells in vivo. Newborn Rag2-/-γc-/- mice were engrafted with ZIKV-infected hematopoietic stem cells (HSC) and monitored for symptoms and lesions. Results Within 13 days, mice displayed outward clinical symptoms that encompassed stunted growth, hunched posture, ruffled fur, and ocular defects. Striking gross pathologies in the brain and visceral organs were noted. Our results also confirmed that ZIKV actively infected human CD34+ hematopoietic stem cells and restricted the development of terminally differentiated B cells. Histologically, there was multifocal mineralization in several different regions of the brain together with ZIKV antigen co-localization. Diffuse necrosis of pyramidal neurons was seen with collapse of the hippocampal formation. Discussion Overall, this model recapitulated ZIKV microcephaly and CZS together with viral adverse effects on the human immune cell ontogeny thus providing a unique in vivo model to assess the efficacy of novel therapeutics and immune interventions.